A strategy for an accurate estimation of the basal permittivity in the Martian North Polar Layered Deposits. (19th September 2016) - Lauro, S.E.; Gennarelli, G.; Pettinelli, E.; Soldovieri, F.; Cantini, F.; Rossi, A.P.; Orosei, R.
ABSTRACT: This paper deals with the investigation of the Mars subsurface by means of data collected by the Mars Advanced Radar for Subsurface and Ionosphere Sounding working at few megahertz frequencies. A data processing strategy, which combines a simple inversion model and an accurate procedure for data selection is presented. This strategy permits to mitigate the theoretical and practical difficulties of the inverse problem arising because of the inaccurate knowledge of the parameters regarding both the scenario under investigation and the radiated electromagnetic field impinging on the Mars surface. The results presented in this paper show that it is possible to reliably retrieve the electromagnetic properties of deeper structures if such strategy is accurately applied. An example is given here, where the analysis of the data collected on Gemina Lingula, a region of the North Polar layer deposits, allowed us to retrieve permittivity values for the basal unit in agreement with those usually associated to the Earth basaltic rocks.